prodgers2 Wrote:I need to figure out how to solve the following problem: (2p)^1/2 * (2p^3)^1/3 can someone help me?
First you will need a hierarchy rule, that is what gets done first. Basically the one we would need is that exponentiation gets done before multiplication. Call it rule H1.
You will also need three distributive rules. One, call it D1, says
D1: (a^x)^y = a^(x*y)
Rule two, call it D2, says
D2: (a*b)^x = (a^x) * (b^x)
Rule 3, call it D3, says
D3: (a^x) * (a^y) = a^(x+y)
Oh, I almost forgot the associative rule for multiplication, i.e. a * b = b * a, which I assume is true for the problems here.
I'll assume 1/2 is one-half and 1/3 is one third.
(2p)^1/2 means (2 * p)^1/2 = (2^1/2) * (p^1/2) by rule D2
By rule H1
(2p^3) = (2 * p^3)
so
(2p^3)^1/3 = 2^1/3 * (p^3)^1/3 by rule D2
= 2^1/3 * p^(3*1/3) = 2^1/3 * p^1 by rule D1
Note that p is the same as p^1 and use the associative rule several times to get
(2p)^1/2 * (2p^3)^1/3 = (2^1/2) * (p^1/2) * 2^1/3 * p
=2^1/2 * 2^1/3 * p^1/2 * p
Finally, use rule D3 to get
=2^1/2 * 2^1/3 * p^1/2 * p = 2^(1/2 + 1/3) * p^(1/2 + 1)
= 2^5/6 * p^3/2
Note: IF (2p^3)^1/3 was supposed to be ((2p)^3)^1/3 that would mean a different (and much simpler) answer but the mechanics of the solution would be the same. Hint: let a = 2p